Episode 39: WCROC Research Update with Dr. Bradley J. Heins: The Moos Room - Heins, Brad; Armstrong, Joe; Krekelberg, Emily (My University, 2020)
If you have been listening to the show you know that we poke fun at Bradley quite a bit. This episode is dedicated to making sure everyone knows that Bradley works hard and has plenty of projects going on at the WCROC Dairy. Hope you enjoy learning a little more about one of our co-hosts.
Runtime 34:26